Experiences of University Students with Covid-19 Regarding the Illness Process - Filiz, Mustafa; Öztürk, Atakan (Bursa Technical University, 2023)
The aim of this study is to evaluate the experiences of university students who have experienced Covid-19 in a versatile way and to develop a scale related to the subject. The sample of the research consists of 120 students who have voluntarily participated in the study, who have had Covid-19. Factor analysis, t-test and Anova tests were performed for the data. It has been observed that the severity of transmission of Covid-19 does not change according to the presence of chronic disease and vaccination status. It has been observed that the severity of the Covid-19 disease does not change according to the economic status of the student, the number of vaccine doses, the Covid-19 vaccine type, the use of medicine recommended by a doctor, and the use of herbal medicine. It has been observed that nearly half of the students trust the Turkish health system, and almost all of them have the Covid-19 vaccine. It has been observed that factors such as following the rules and being vaccinated are followed in the fight against Covid-19. It has been observed that factors such as vaccine, type of vaccine and medication do not affect the severity of the disease.

Bu çalışmada amaç, Covid-19 geçirmiş üniversite öğrencilerinin deneyimlerini çok yönlü olarak değerlendirmek ve konu ile ilgili bir ölçek geliştirmektir. Araştırmanın örneklemini çalışmaya gönüllü olarak katılan Covid-19 geçirmiş 120 öğrenci oluşturmaktadır. Verilere yönelik faktör analizi, t testi ve Anova testleri yapılmıştır. Covid-19’u geçirme şiddetinin kronik hastalığın var olup olmaması ve aşı olma durumuna göre değişmediği görülmüştür. Covid-19 hastalığını geçirme şiddetinin öğrencinin ekonomik durumu, aşı doz sayısı, Covid-19 aşı türü, doktor tavsiyeli ilaç kullanma durumu ve bitkisel ilaç kullanım durumuna göre değişmediği görülmüştür. Öğrencilerin Türkiye sağlık sistemine yarısına yakının güvendiği, neredeyse tamamının Covid-19 aşısı olduğu olduğu görülmüştür. Covid-19 ile mücadelede kurallara uyulması, aşı olma gibi faktörlere uyulduğu görülmüştür. Aşı, aşı türü, ilaç gibi faktörlerin hastalığın şiddeti üzerinde etkili olmadığı görülmüştür.
COVİD-19 GEÇİRMİŞ ÜNİVERSİTE ÖĞRENCİLERİNİN HASTALIK SÜRECİNE İLİŞKİN DENEYİMLERİ